2017
DOI: 10.1037/law0000125
|View full text |Cite
|
Sign up to set email alerts
|

Logical but incompetent plea decisions: A new approach to plea bargaining grounded in cognitive theory.

Abstract: Although much research considers the cognitive processes involved in legal decision making of jurors and judges, decisions to accept or reject plea bargains have received far less attention. We examine decisions in plea scenarios to test predictions of Fuzzy-Trace Theory regarding how cognitive processing style (specifically, greater reliance on gist or verbatim representations) affects plea decisions and how this could lead to suboptimal decision making, especially among defendants who are young adults. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 39 publications
(72 reference statements)
4
56
0
Order By: Relevance
“…While results from a single, tightly controlled study must be interpreted with caution, it is encouraging that by separating and fully crossing the effects of discount and potential trial sentence, we appear to have gained additional insight into how these variables might be exerting their effects on plea decisions (at least under the conditions of out experiment). Our data on the effect of plea discount are in line with existing research on categorically different, substantially reduced, or lenient offers (Bordens, ; Helm & Reyna, ; Russano, Meissner, Narchet, & Kassin, ) and have important implications for wrongful conviction research – for example, Redlich, Yan, Norris, and Bushway () recently reviewed 500 district attorney case files in New York State and found that individuals who deny their charges tend to receive the most steeply discounted plea offers. Moreover, no state legislature, save for New York, has placed any explicit restriction on sentence differentials in plea offers (Zottoli et al ., ).…”
Section: Resultssupporting
confidence: 85%
“…While results from a single, tightly controlled study must be interpreted with caution, it is encouraging that by separating and fully crossing the effects of discount and potential trial sentence, we appear to have gained additional insight into how these variables might be exerting their effects on plea decisions (at least under the conditions of out experiment). Our data on the effect of plea discount are in line with existing research on categorically different, substantially reduced, or lenient offers (Bordens, ; Helm & Reyna, ; Russano, Meissner, Narchet, & Kassin, ) and have important implications for wrongful conviction research – for example, Redlich, Yan, Norris, and Bushway () recently reviewed 500 district attorney case files in New York State and found that individuals who deny their charges tend to receive the most steeply discounted plea offers. Moreover, no state legislature, save for New York, has placed any explicit restriction on sentence differentials in plea offers (Zottoli et al ., ).…”
Section: Resultssupporting
confidence: 85%
“…Scholars supporting plea bargaining have argued that innocent defendants would be unlikely to find plea offers attractive, going as far as to describe the problem of innocent defendants pleading guilty as “barely a perceptible theoretical ripple” when compared with other costs in the plea-bargaining system (Easterbrook, 1992; Schulhofer, 1992). However, accumulating research suggests that innocent defendants might be pleading guilty fairly frequently (for example Dervan & Edkins, 2013; Grisso et al, 2003; Helm & Reyna, 2017; Tor, Gazal-Ayal, & Garcia, 2010). Our results support this accumulating research.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of deciding which option (plea or trial) is preferable to a defendant, empirical research has confirmed that risk preferences (Bjerk, 2008), probabilities of conviction (Tor, Gazal-Ayal, & Garcia, 2010), and potential sentences (Bordens & Bassett, 1985) influence defendant decisions. However, research also suggests that defendants are influenced by whether they are guilty or innocent (Helm & Reyna, 2017; Tor at al., 2010), pressure from the prosecutor, expediency, and acquiescence (including acquiescing with attorney advice) (Bordens & Bassett, 1985). This makes the plea decision a complex one that is influenced by defendant psychology and attorney practice, as well as by the options involved (Burke, 2007; Covey, 2007; Helm & Reyna, 2017).…”
Section: The Plea Decisionmentioning
confidence: 99%
See 2 more Smart Citations